Efektifitas Buah Asam Kandis (Garcinia diocia Blume) sebagai Bahan Penggumpal dan Pengawet pada Produk Tahu - Ilhamsyah Azri; Akhyar Ali; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to obtain the best concentration from kandis acid as a coagulant agent and preservative in tofu product. Thisresearch used a Completely Randomized Design (CRD) with six treatments and three replications, followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%.The treatment of this researchwereAK1 (the concentration of the kandis acid solution 7,5%),AK2 (the concentration of the kandis acid solution10,0% ), AK3 (the concentration of the kandis acid solution 12,5%), AK4 (the concentration of the kandis acid solution 15,0%), AK5 (the concentration of the kandis acid solution 17,5%) andAK6 (the concentration of the kandis acid solution 20,0%). The analysis observed were acidity (pH), protein, total bacteria, descriptive and hedonic sensory tests of taste, color and softness.The best treatment of this research was the concentration of 15% kandis acid solution which has acidity level (pH) of 4.58, protein 15.65%, total bacteria 8.22 Cfu/ml, taste not sour, slightly color and slightly soft texture. Keyword :kandis acid, tofu,coagulant agent, preservative